ANALISIS FORMULA TERHADAP POPULARITAS NOVEL THE KITE RUNNER KARYA KHALED HOSSEINI (AN ANALYSIS OF FORMULA TOWARDS THE POPULARITY OF THE KITE RUNNER NOVEL BY KHALED HOSSEINI) - Endang Endang Suciati (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2015)
Abstrak Novel